Les substances d'origine végétale en Côte d'Ivoire Potentiel et développement durable - Kati-Coulibaly, Séraphin; Békro, Yves-Alain; Boisvert, Valérie; Koné, Mamidou Witabouna; Pabst, Jean-Yves (Expertise collective, 2022)
The abundance, uniqueness and diversity of plant-based species in Côte d'Ivoire has enabled the Ivorian people to amass a large and varied amount of knowledge related to plant-derived substances, including notably with regard to medical, cosmetic, aromatic and nutritional use. However, for a number of decades now Ivorian biodiversity has seen a steady degradation, with its forest canopy increasingly under threat. This has resulted in the sustainable exploitation of Ivorian natural resources, and such benefits as may be derived from them by the Ivorian people, being compromised. It is within this context that the Ivorian Ministry of Higher Education and Scientific Research (MESRS) entrusted to IRD the task of undertaking a joint scientific assessment of the potential inherent in natural plant-based substances in Côte d'Ivoire. In response, IRD assembled for this purpose a multidisciplinary committee of experts in pharmacognosy, phytochemistry, nutrition, microbiology and environmental economics, as well as anthropologists and specialists in the field of African pharmacological plants. The assessment deals with non-wood-based plants and products derived from them, the aim being to produce an up-to-date inventory of the subject matter and to identify strategies for their sustainable exploitation. Based on data gathered, the expert committee has put forward 17 recommendations aimed at producing a clear elucidation of the government's environmental policies and preserving biodiversity, all while ensuring public health and economic development.